Fotografía tomada en comedor de casa - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1928)
SPANISH: Fotografía de la familia Morey tomada en comedor de casa
ENGLISH: Photograph of the Morey family taken in the dining room of the house.

SPANISH: Fotografía de la familia Morey tomada en comedor de casa
ENGLISH: Photograph of the Morey family taken in the dining room of the house.
Photograph taken in the dining room of the house
Keywords: Iquitos (Perú)|~|Upper class families--Photograph Albums|~|Albúm de la Familia "Morey"|~|Iquitos (Perú)|~|familia de la clase alta|~|album de fotografías